The evolving biology and treatment of prostate cancer - Russel S. Taichman; Robert D. Loberg; Rohit Mehra; Kenneth J. Pienta (The Journal of Clinical Investigation, 2007)
Since the effectiveness of androgen deprivation for treatment of advanced prostate cancer was first demonstrated, prevention strategies and medical therapies for prostate cancer have been based on understanding the biologic underpinnings of the disease. Prostate cancer treatment is one of the best examples of a systematic therapeutic approach to target not only the cancer cells themselves, but the microenvironment in which they are proliferating. As the population ages and prostate cancer prevalence increases, challenges remain in the diagnosis of clinically relevant prostate cancer as well as the management of the metastatic and androgen-independent metastatic disease states.